Data Mining Tingkat Kepatuhan Pasien Tuberkulosis dalam Menjalani Pengobatan Mengunakan Agloritma C4.5 - Muhammad Ridho; Della Zilfitri; Felka Andini; Yosep Filki (SEULANGA SYSTEM PUBLISHER, 2023)
The high number of TB cases in the work area of ​​the Bukittinggi City Health Service Puskesmas Nilam Sari. The number of patients who do not comply with TB treatment. This study was conducted to determine the level of patient compliance in undergoing TB treatment so that the results of the study become input for medical personnel in charge of TB at Nilam Sari Health Center in policy making. The C4.5 method was used in this study to classify the data of compliant and non-adherent TB patients in undergoing treatment at the Nilam Sari Health Center. The data from TB patient visits to the Puskesmas were analyzed using the C4.5 method to obtain new knowledge from the TB patient visit data to the Puskesmas. The data analyzed consisted of attributes of the visit schedule, environmental distance, age which influenced the decision criteria for the level of adherence of TB patients in undergoing treatment at the Nilam Sari Health Center. The decision criteria for the results of TB patient visits consist of